Transcutaneous Spinal Cord Stimulation Improves Respiratory Muscle Strength and Function in Subjects with Cervical Spinal Cord Injury: Original Research - Kumru, Hatice; García-Alén, Loreto; Ros-Alsina, Aina; Albu, Sergiu; Valles, Margarita; Vidal, Joan (Biomedicines, 2023)
(1) Background: Respiratory muscle weakness is common following cervical spinal cord injury (cSCI). Transcutaneous spinal cord stimulation (tSCS) promotes the motor recovery of the upper and lower limbs. tSCS improved breathing and coughing abilities in one subject with tetraplegia. Objective: We therefore hypothesized that tSCS applied at the cervical and thoracic levels could improve respiratory function in cSCI subjects; (2) Methods: This study was a randomized controlled trial. Eleven cSCI subjects received inspiratory muscle training (IMT) alone. Eleven cSCI subjects received tSCS combined with IMT (six of these subjects underwent IMT alone first and then they were given the opportunity to receive tSCS + IMT). The subjects evaluated their sensation of breathlessness/dyspnea and hypophonia compared to pre-SCI using a numerical rating scale. The thoracic muscle strength was assessed by maximum inspiratory (MIP), expiratory pressure (MEP), and spirometric measures. All assessments were conducted at baseline and after the last session. tSCS was applied at C3-4 and Th9-10 at a frequency of 30 Hz for 30 min on 5 consecutive days; (3) Results: Following tSCS + IMT, the subjects reported a significant improvement in breathlessness/dyspnea and hypophonia (p < 0.05). There was also a significant improvement in MIP, MEP, and forced vital capacity (p < 0.05). Following IMT alone, there were no significant changes in any measurement; (4) Conclusions: Current evidence supports the potential of tSCS as an adjunctive therapy to accelerate and enhance the rehabilitation process for respiratory impairments following SCI. However, further research is needed to validate these results and establish the long-term benefits of tSCS in this population.